2021
DOI: 10.1111/phn.12954
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards social distancing in response to COVID‐19

Abstract: Objectives: COVID-19 has highlighted differences in our engagement in health prevention behaviors. The Health Belief Model (HBM), personality traits (conscientiousness, extraversion, and neuroticism), and sociodemographic variables were used to evaluate social distancing during the first month of a state-mandated Stay At Home (SAH) order.Design: A web-based convenience sample of 645 Ohioans was surveyed. Hierarchical linear regression and mediation analysis were used to examine predictors of social distancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…During the COVID-19 pandemic, adherence to physical distancing was related to sense of personal responsibility or control over one’s own behavior [ 34 ], whereas decreased psychosocial well-being and lack of social support were associated with non-adherence to physical distancing [ 35 ]. Viral anxiety was also associated with adherence to physical distancing [ 36 , 37 ]. People who felt anxious about being infected with viruses tended to adhere to physical distancing.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, adherence to physical distancing was related to sense of personal responsibility or control over one’s own behavior [ 34 ], whereas decreased psychosocial well-being and lack of social support were associated with non-adherence to physical distancing [ 35 ]. Viral anxiety was also associated with adherence to physical distancing [ 36 , 37 ]. People who felt anxious about being infected with viruses tended to adhere to physical distancing.…”
Section: Discussionmentioning
confidence: 99%
“…41 Conversely, individuals who feel anxious about viral infection are more likely to adhere to physical distancing policies. 19 Conversely, depression was significantly associated with cores of the total scale and three scale factors. The relationship between depression and social distancing phobia is somewhat complicated.…”
Section: Age Viral Anxiety Depression and Social Distancing Phobiamentioning
confidence: 95%
“…In this COVID-19 pandemic, viral anxiety might also be an important factor governing adherence to physical distancing rules since it can influence an individual's physical distancing behavior. 19 Recently, it was reported that anxious people are more likely to adhere to physical distancing policies. 9,20 Social distancing phobia, referring to the excessive anxiety of viral infection while being in public, is speculated to be associated with viral anxiety, though this association has not been well demonstrated yet.…”
Section: Intolerance Of Uncertainty Viral Anxiety and Physical Distan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the COVID-19 pandemic, viral anxiety has been reported to be associated with adherence to or compliance with physical distancing. Anxiety may influence people's physical activity and time spent outdoors ( 12 ); thus, it has been reported that people who feel anxiety tend to adhere to physical distancing ( 13 15 ). “Sodisphobia,” or viral anxiety, is defined as experiencing excessive anxiety of being infected with viruses while in public ( 15 ).…”
Section: Introductionmentioning
confidence: 99%